Use of chemotherapy and loco-regional therapy in stage IA triple-negative breast cancer and their association with oncologic outcomes: A cancer registry study - Pfob, André; Surovtsova, Irina; Kokh, Daria B.; Heil, Jörg; Banys-Paluchowski, Maggie; Morakis, Philipp (International journal of cancer, 2024)
We aimed to evaluate the role of adjuvant chemotherapy and loco-regional therapy for stage IA (pT1, pN0) triple-negative breast cancer (TNBC) in a real-world setting. We identified patients with pT1, pN0 TNBC diagnosed between 2009 and 2021 within the Baden-Württemberg cancer registry (BWCR), Germany. Overall survival (OS) was assessed using Kaplan-Meier statistics and multivariate Cox regression models (adjusted for age, use of chemotherapy, local therapy (breast conserving therapy [breast conserving surgery + radiotherapy] vs. mastectomy), and tumor histologic subtype). A total of 1231 patients with a median follow-up of 45.9 months were identified: 1.0% (12 of 1231) with pT1mi stage, 9.5% (117 of 1231) with pT1a, 23.7% (292 of 1231) with pT1b, and 65.8% (810 of 1231) with pT1c. Multivariate Cox regression analysis revealed no significant influence for the use of chemotherapy on OS in pT1b patients (HR 0.90, 95% CI 0.43-1.90). For pT1c patients with Grade 1-2 tumors, the use of chemotherapy was not significantly associated OS (HR 1.01, 95% CI 0.48-2.11) but breast conserving therapy was associated with improved OS (HR 0.41, 95% CI 0.18-0.93). For pT1c patients with Grade 3 tumors, the use of chemotherapy (HR 0.51, 95% CI 0.33-0.78) as well as breast conserving therapy (HR 0.42, 95% CI 0.23-0.76) was associated with OS. This data suggests that OS in stage IA TNBC is strongly influenced by local therapy rather than the use of chemotherapy, except for pT1c patients with Grade 3 tumors. Larger studies with longer-term follow-up are welcomed to fully inform this discussion.